2020
DOI: 10.3390/jof6040282
|View full text |Cite
|
Sign up to set email alerts
|

Post-Flood Impacts on Occurrence and Distribution of Mycotoxin-Producing Aspergilli from the Sections Circumdati, Flavi, and Nigri in Indoor Environment

Abstract: Mycotoxin-producing Aspergilli (Circumdati, Flavi, and Nigri), usually associated with contaminated food, may also cause respiratory disorders and are insufficiently studied in water-damaged indoor environments. Airborne (N = 71) and dust borne (N = 76) Aspergilli collected at post-flood and control locations in Croatia resulted in eleven different species based on their calmodulin marker: A. ochraceus, A. ostianus, A. pallidofulvus, A. sclerotiorum, and A. westerdijkiae (Circumdati); A. flavus (Flavi); and A.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Flooding before the maize harvest in Argentina resulted in more than 65% of samples tested being above the mycotoxin risk threshold [ 59 ]. Jakšić et al [ 60 ] exclusively reported the presence of aflatoxigenic species A. flavus at post-flood locations. Since water is a major promoter of fungal proliferation [ 61 ], the expected aftermath of flooding is even higher, as the occurrence of flood creates a moist environment conducive for fungal growth and mycotoxin production.…”
Section: Possible Sources Of Mycotoxin Exposure To Humans and Animalsmentioning
confidence: 99%
“…Flooding before the maize harvest in Argentina resulted in more than 65% of samples tested being above the mycotoxin risk threshold [ 59 ]. Jakšić et al [ 60 ] exclusively reported the presence of aflatoxigenic species A. flavus at post-flood locations. Since water is a major promoter of fungal proliferation [ 61 ], the expected aftermath of flooding is even higher, as the occurrence of flood creates a moist environment conducive for fungal growth and mycotoxin production.…”
Section: Possible Sources Of Mycotoxin Exposure To Humans and Animalsmentioning
confidence: 99%
“…Additionally, the exclusive identification by MEA of Aspergillus sections Fumigati and Flavi and Circumdati section in DG18 increases the importance of applying different culture media to acknowledge the Aspergillus contribution to fungal contamination [32]. In fact, the presence indoors of Aspergillus section Fumigati represents a major risk for the onset and development of respiratory diseases in immunocompromised individuals [47,48], while sections Flavi and Circumdati, major producers of aflatoxin B1 and ochratoxin, respectively, represent the potential exposure to these mycotoxins [3,44,49].…”
Section: Fungal Contamination Assessmentmentioning
confidence: 99%
“…Atmosphere 2021, 12, x FOR PEER REVIEW 7 of 16 onset and development of respiratory diseases in immunocompromised individuals [47,48], while sections Flavi and Circumdati, major producers of aflatoxin B1 and ochratoxin, respectively, represent the potential exposure to these mycotoxins [3,44,49].…”
Section: Fungal Contamination Assessmentmentioning
confidence: 99%
“…Because of their biomedical and economical significance, special importance among indoor Aspergilli is given to those from the section Flavi and series Nigri (ex-section Nigri ) and Versicolores (ex-section Versicolores ), among which A. flavus , A. tubingensis , A. welwitschiae , A. jensenii and A. creber are the most commonly identified species [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. The ability to tolerate a range of the water activities (a w ) 0.75–0.90, a wide range of pH and ionic strength make Aspergilli particularly common indoor fungi [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Indoor dust contains both indoor and outdoor fungi brought from various outdoor sources and thus it is the most representative sample for assessment of human exposure [ 29 ]. Aspergilli from the section Flavi and series Nigri and Versicolores have been frequently identified in indoor dust samples from around the world [ 13 , 30 , 31 , 32 ]. In addition, Aspergilli metabolites have also been identified in various indoor dust samples [ 9 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%